Exact speed tracking realization of the single shaft micro-turbine system via higher-order sliding mode observer - Sun, Yuge (2018)
We present in this paper, a composite control approach to realize the exact speed trajectory tracking for the single shaft micro-turbine (MT) system. The composite controller is developed by incorporating a higher-order sliding mode observer and a feedback domination technique. By mean of the proposed method, asymptotic stability of the MT system can be ensured even in the presence of mismatched disturbances. It is illustrated, by numerical simulations, how this handy machinery is feasible for the practical disturbed MT system to realize the exact tracking, rather than a practical tracking objective.